Effects of experimental hypervitaminosis D3 on renal effects of intragastral and parenteral injection of zinc chloride - R. T. Tsallaeva; V. B. Brin (Кубанский научный медицинский вестник, 2014)
The objective was to study the effect of hypercalcemia on the changes of renal function due to intragastric and subcutaneous administration of zinc chloride. Hypercalcemia was modeled in rats by introducing them an aqueous solution of vitamin D3 at a dose of 3000 МЕ (0,2 ml)/100 g for 30 days. Zinc chloride was administered intragastrally and subcutaneously at a dose of 20 mg/kg daily for 30 days. The study found that hypercalcemia leaded to more severe manifestations of toxic nephropathy in rats with intragastric administration of zinc chloride and in rats with subcutaneous administration of metal, however, it leaded to lower damaging effect on the kidneys.